Geneva Cocktail for Cytochrome P450 and P‐Glycoprotein Activity Assessment Using Dried Blood Spots. Issue 3 (10th April 2014) - Bosilkovska, M; Samer, C F; Déglon, J; Rebsamen, M; Staub, C; Dayer, P; Walder, B; Desmeules, J A; Daali, Y
<x xml:space="preserve">Abstract</x> The suitability of the capillary dried blood spot (DBS) sampling method was assessed for simultaneous phenotyping of cytochrome P450 (CYP) enzymes and P‐glycoprotein (P‐gp) using a cocktail approach. Ten volunteers received an oral cocktail capsule containing low doses of the probes bupropion (CYP2B6), flurbiprofen (CYP2C9), omeprazole (CYP2C19), dextromethorphan (CYP2D6), midazolam (CYP3A), and fexofenadine (P‐gp) with coffee/Coke (CYP1A2) on four occasions. They received the cocktail alone (session 1), and with the CYP inhibitors fluvoxamine and voriconazole (session 2) and quinidine (session 3). In session 4, subjects received the cocktail after a 7‐day pretreatment with the inducer rifampicin. The concentrations of probes/metabolites were determined in DBS and plasma using a single liquid chromatography–tandem mass spectrometry method. The pharmacokinetic profiles of the drugs were comparable in DBS and plasma. Important modulation of CYP and P‐gp activities was observed in the presence of inhibitors and the inducer. Minimally invasive one‐ and three‐point (at 2, 3, and 6 h) DBS‐sampling methods were found to reliably reflect CYP and P‐gp activities at each session. Clinical Pharmacology & Therapeutics (2014); 96 3, 349–359. advance online publication 7 May 2014. doi:10.1038/clpt.2014.83